University Technology Platform of Anticipatory Learning - Gitelman, Leonid Davidovich; Sandler, Daniil Gennadyevich; Kozhevnikov, Mikhail Viktorovich (Economy of Regions, 2016)
The innovative development sets large-scale and challenging tasks, which need to be addressed in the lack-of-knowledge conditions and require the coordination and integration of numerous expert structures, which are scattered around the world and have different status and competencies. One of the mechanisms of integrating the partners' intellectual and financial resources is provided by the technology platforms. The article discusses the nature and functions of technology platforms and analyzes the experience of their application in different countries with a special emphasis on universities. The article gives an overview of the various interpretations of technology platform concepts. It also describes the development and implementation of the technological platform at the Ural Federal University (research and education centre ‘ENGEC'), which was targeted at organizing anticipatory learning in the sphere of energy engineering and high-tech industries; its mechanism and role in improving different university activities and processes are shown. This platform is based on the original methodology ‘Integrated System of Consulting, Training, and Transformation' (ISCT), which includes authentic methods and technologies, which are used in the educational process. A significant advantage of this methodology is that it can be applied in university education as well as in corporate training integrated with innovative activities.